MEDIATIZATION OF ARTIFICIAL INTELLIGENCE CONCEPT IN THE RUSSIAN LANGUAGE MEDIA DISCOURSE: CORPUS-BASED APPROACH - Elena Yu. Ilyinova; Larisa A. Kochetova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
Based on corpus-assisted discourse analysis, the paper studies the mediatization of artificial intelligence (AI) technology in the Russian-language media discourse as a construe technique that shapes AI perception and evaluation as a concept of new social reality. The paper reveals linguistic portraying of the AI concept in Russian digital media corpus, construed by business-oriented outlets Kommersant, Vedomosti, RBC, and popular media resources, such as Lenta.ru, Argumenty i Fakty, Komsomolskaya Pravda. Corpus-assisted discourse analysis comprises aims to extract the quantitative parameters of texts and establish their correlations with content parameters; define the themes of narratives about AI, which determine its discursive interpretation, and describe their distribution across the Russian-language news digital corpus; define discursive strategies used for designing the image of AI. The quantitative characteristics of the texts construing AI imagery in the corpus under study point to the prevalence of small and moderate size texts, which is explained by the pragmatics of informing a broad lay audience on advancement and development of AI without initiating any public discussions. The thematic distribution analysis showed domination of “Positive AI capabilities” and “AI development and Investments”, whereas “Impending danger” and “Negative AI capabilities” are covered infrequently. Argumentation in the explanatory and prognostic strategies introduces the topoi of inevitability, necessity, and rivalry in AI development. The explanatory strategy expands on the nature of AI, its functions and potential. The prognostic strategy delivers information on the development and advancement of AI technology, portraying efficiency scenarios, but only a tiny fraction of the texts warn about the negative consequences of AI. The novelty of the results lies in the establishment of contradictory mediatization of the AI concept, which, on the one hand, is aimed at depicting its positive portrayal and capability of bringing social and economic benefits. On the other hand, it contains a warning about its potential dangers and risks if the spheres of its application expand.